Effectiveness of Hypertension Management through Early Detection, Hypertension Education, and Hypertension Exercise. - Tarisa, Tarisa; Yamin, Ahmad; Juniarti, Neti (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
Hypertension is one of the leading Non-Communicable Diseases (NCDs) causing cardiovascular complications in Indonesia. This study aims to evaluate the effectiveness of hypertension management through early detection, health education, and hypertension exercise interventions. A pre-experimental design was used with a community nursing care approach. The intervention included early detection and hypertension education for 55 residents, as well as hypertension exercise involving 15 residents, with blood pressure measured before and after the intervention. Data were analyzed using bivariate analysis. Results showed that early detection identified a prevalence of 49.1% of respondents as severely overweight, 29.1% with grade 2 hypertension, and 9.1% with blood glucose levels >200 mg/dL. Unhealthy lifestyle habits included high sodium intake (69.1%), sugar (60%), fat (45.5%), while only 25.5% consumed vegetables and fruits adequately, 52.7% had low physical activity, and 10.9% were smokers. Hypertension education significantly increased knowledge scores from 5.33 to 7.69 (p = 0.000), and hypertension exercise significantly reduced systolic blood pressure from 129.47 mmHg to 122.73 mmHg (p = 0.000), and diastolic pressure from 83.53 mmHg to 81.13 mmHg (p = 0.027). Hypertension management through early detection, education, and exercise proved effective in increasing knowledge and reducing blood pressure among residents.